Upaya Meningkatkan Keaktifan Belajar Siswa Melalui Guided Inquiry Pada Mata Pelajaran IPA Pada Kelas V SD Negeri 0119 Banjar Raja - Lailan Aprina Siregar; Riski Hamdan Saputra; Abdur Rahman Daulay (STIKes Ibnu Sina Ajibarang, 2023)
The aim of this research is: to determine efforts to increase student learning activity through guided inquiry in science subjects in class V of SD Negeri 0119 Banjar Raja. Learning will be meaningful if learning activities are designed to foster student learning activity. The results of observations in class V of SD Negeri 0119 Banjar Raja show that student learning activity in science subjects is still low. This research aims to increase students' active learning through guided inquiry in science subjects in class V of SD Negeri 0119 Banjar Raja. This type of research is collaborative classroom action research. The subjects in this research were 40 class V students at SD Negeri 0119 Banjar Raja, consisting of 20 male students and 20 female students. This research design uses the Kemmis and Mc Taggart (1988) model. Data collection methods through observation, documentation and interviews. Data analysis techniques were carried out descriptively qualitatively and quantitatively. The research results showed that student learning increased after being given learning actions using the guided inquiry strategy. Students' activeness in answering questions increased after providing feedback from the teacher. Students' activeness in proposing hypotheses increased after guidance from the teacher. Student activity in collecting data is carried out by providing opportunities to make maximum use of learning resources and search for various information in solving problems. Students' active learning in processing data increased after guidance and additional time given by the teacher. Student activity in solving problems increased after giving worksheets to each student. Student learning activity in science learning using guided inquiry in class V of SD Negeri 0119 Banjar Raja increased by 25%, namely in cycle I of 54.17% (13 students) to 79.17% (19 students) and was included in the very high category. The actions in this research were stopped and said to be successful in cycle II because they had reached the success criteria.